Collegiate football player achilles tendon blood flow tends to increase throughout time in D1 college football - Davidson, G. K.; Hinkle, L. J; Schaugaard, B. T. T.; Wilwand, M.; Mortensen, B. B.; Johnson, A. W. (International Journal of Exercise Science Conference Proceedings, 2025)
Achilles tendon health is crucial for athletic performance, particularly in high-impact sports such as football. Investigating the physiological changes in blood flow that the tendon undergoes as a result of a single training session may provide insight into tendon health and understanding the balance between injury prevention and performance optimization.